BEHAVIORAL BIASES, FINANCIAL LITERACY AND INVESTMENT DECISION-MAKING - Michelle Charline Wibowo; Luky Patricia Widianingsih (Jurnal Akuntansi Kontemporer, 2025)
Research Purposes. This study aims to determine the effects of Self-Control, Overconfidence, Herding, and Mental Accounting on Investment Decisions, with Financial Literacy Serving as a moderating variable. Research Methods. The data analysis method used multiple linear regression analysis. Research Results and Findings. The results show that there is a significant effect of self-control and overconfidence on the investment decisions of young investors. Herding has no significant effect on investment decisions due to the tendency of investors to make decisions independently. Mental accounting has no significant effect on investment decisions; good planning in mental accounting does not mean that it will make investors consider every decision taken. The moderating role of financial literacy in self-control, overconfidence, and herding in investment decisions has an insignificant effect. Meanwhile, financial literacy can weaken the negative influence of mental accounting in investment decision-making. The implication of this research is the importance of strengthening self-control and education to control overconfidence in the investment decisions of young investors.